Transformasi strategis sistem informasi keperawatan di rumah sakit X menuju smart garden hospital - Wea, Maria Eka Brigida Wonga; Septirini, Maria Indah; Suhani, Nini; Perdana, Riska Rusfita; Septianata, Viesca; Hariyati, Roro Tutik Sri (Holistik Jurnal Kesehatan, 2025)
Background: A smart garden hospital is an approach that prioritizes not only smart technology but also environmental sustainability, patient comfort, humanization of services, and operational efficiency based on information technology. Information and communication technology supports evidence-based nursing practice, strengthens patient safety, and meets global healthcare standards. Purpose: To describe the strategic transformation of X hospital nursing information system toward a smart garden hospital. Method: The field study used a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis approach. Data were analyzed using Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, and mapped onto an Internal-External (IE) matrix to determine the organization's strategic position. Results: The analysis yielded an IFE score of 2.61 and an EFE score of 3.15, placing Hospital X in the "growth and development" quadrant, representing an organization with adequate internal strengths and strong external opportunities, making an aggressive growth strategy an appropriate choice. Conclusion: The transformation of X hospital nursing information system emphasizes the importance of a comprehensive strategy involving strengthening human resource capacity, optimizing technology, and responsive risk management. Suggestion: Hospitals can formulate strategies based on the Balanced Scorecard (BSC) perspective and key performance indicators (KPIs) linked to the TOWS strategy in developing their nursing management information systems.   Keywords: Information; Hospital; Nursing; Smart Garden Hospital; Strategy; System; Transformation.   Pendahuluan: Smart garden hospital merupakan sebuah pendekatan yang tidak hanya mengedepankan teknologi cerdas, tetapi juga memperhatikan keberlanjutan lingkungan, kenyamanan pasien, dan humanisasi pelayanan serta efisiensi operasional berbasis teknologi informasi. Teknologi informasi dan komunikasi untuk mendukung praktik keperawatan berbasis bukti, memperkuat keselamatan pasien, serta menjawab standar global pelayanan kesehatan. Tujuan: Untuk mendeskripsikan transformasi strategis sistem informasi keperawatan di rumah sakit X menuju smart garden hospital. Metode: Studi lapangan dengan pendekatan analisis Strength, Weakness, Opportunity, and Threat (SWOT). Data dianalisis menggunakan matriks internal faktor evaluasi (IFE) dan eksternal faktor evaluasi (EFE), serta dipetakan ke dalam matriks internal-eksternal (IE) untuk menentukan posisi strategis organisasi. Hasil: Analisis didapatkan skor IFE = 2.61 dan Skor EFE = 3.15, menempatkan rumah sakit X pada kuadran "growth and build" yang merepresentasikan organisasi dengan kekuatan internal yang cukup dan peluang eksternal yang kuat, sehingga strategi pertumbuhan agresif menjadi pilihan yang sesuai. Simpulan: Transformasi sistem informasi keperawatan rumah sakit X menegaskan pentingnya strategi komprehensif yang melibatkan penguatan kapasitas sumber daya manusia, optimalisasi teknologi, dan manajemen risiko yang responsif. Saran: Rumah sakit dapat melakukan perumusan strategis yang ditetapkan melalui perspektif balance scorecard (BSC) dan key performance indicators (KPI) yang dikaitkan dengan strategi TOWS dalam pengembangan sistem informasi manajemen keperawatan.   Kata Kunci: Informasi; Keperawatan; Rumah Sakit; Smart Garden Hospital; Strategis; Sistem; Transformasi.